Evaluasi Antioksidan Minuman Kopi yang Dikombinasikan dengan Ekstrak Gambir dan Madu: Antioxidant Evaluation of Coffee Beverages Combined with Gambier Extract and Honey - Jannah, Syerina Raihatul; Verawati, Endang; Manurung, Nancy Eka Putri; Ichsan, Onne Akbar Nur (Universitas Bumigora, 2025)
Free radicals are molecules with unpaired electrons that can trigger various serious diseases. Therefore, antioxidant intake through food and beverages is essential to prevent free radical-induced damage. This study aimed to analyze the effect of coffee, gambir extract, and honey on antioxidant levels to support health improvement. A completely randomized design (CRD) with a single factor, nonfactorial method was used, focusing on different ratios of coffee powder combined with gambir extract and honey. Five treatment formulations were tested: 100% coffee (control) and combinations with 2.5%, 5%, 7.5%, and 10% of gambir extract and honey. Each treatment was replicated three times. The observed parameters included pH, solubility, total phenol content, and antioxidant activity (IC50 value). The results showed that the combination significantly affected all the observed parameters. The values obtained ranged from pH 6.21 to 6.33, solubility from 27.40% to 31.72%, total phenol from 8.40 mg / ml to 78.53 mg / ml and IC50 from 117.89 ppm to 563.06 ppm. Therefore, the conclusion of this study is that the addition of gambir extract and honey can enhance antioxidant activity and increase the inhibition of free radicals in coffee beverages. This research is expected to contribute to the development of functional drinks.